Strategy to combat extremism in Iraq and the role of information technology (قضايا سياسية, 2024)
Extremism is a dangerous phenomenon that threatens stability, peace, and national unity, and hinders the wheel of development, the collective security system, and international peace and security. The danger of the phenomenon also lies in its ability to recruit and numb the minds of young people. Therefore, the study stems from our urgent need to gather all the facts related to the origins of extremism and terrorism, and the motives for their penetration and spread. And their strengths, and their current weaknesses, and since electronic terrorism is the use of the digital computer with its systems, programs, accessories, and means of communication to commit terrorist crimes, the Internet has turned into an “alternative media” for terrorist gangs, and the Iraqi government must have a number of promising counter-extremism policies. Which it can quote to formulate its own strategy in combating extremism after the defeat of ISIS. The researchers recommend that the government benefit from the spirit of national unity that still dominates the Iraqi street in the wake of the defeat of the organization, and to aspire to strengthen the Iraqi identity in order to achieve consensus and reform between the different groups without Being infiltrated by extremist agendas.